THEORETICAL FOUNDATION OF ADAPTIVE MANAGEMENT OF BUSINESS PROCESSES IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY OF UKRAINE - UMANETS, Tetyana; DARIIENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to develop the theoretical and conceptual foundations of adaptive management of business processes in the conditions of digitalization of the economy of Ukraine. The work improved the conceptual and categorical apparatus of the theory of adaptive management of business processes in the context of digitalization of the economy; the principles and criteria of adaptive management of business processes in conditions of digitalization are determined; the conceptual scheme of adaptive management of business processes based on the system-activity approach is substantiated, and a number of problematic issues that need to be resolved in the study of adaptive management of business processes in the context of the digitalization of the Ukrainian economy are identified. The paper presents the main hypothesis of this study. The concept of "adaptation" is identified according to systemic, process and reflexive approaches. The theory of adaptive management of business processes has been improved by introducing such concepts as: business process at the micro- and meso-levels in the era of digitalization of the economy of Ukraine; competence potential in the conditions of digitalization of the economy; adaptive management of the business process in the conditions of the impact of digitalization on business processes; reflexive and active environment of interaction and coordination of business processes in the era of digital transformation. Five blocks of theoretical and conceptual foundations of adaptive management of business processes in the conditions of digitalization of the economy are proposed and substantiated: 1) prerequisites for adapting business process management to the requirements of digitalization of the economy; 2) conceptual and categorical apparatus of the theory of adaptive management of business processes in the context of digitalization of the economy; 3) principles and criteria of adaptive management of business processes in conditions of digitalization; 4) problematic issues of adaptive management of business processes in the conditions of digitalization of the economy based on the system-activity approach; 5) subsystems of performance indicators of adaptive management of business processes in conditions of digitalization. Ways of further research on this issue are identified.